FLOUTING CONVERSATIONAL MAXIM IN “THE TONIGHT SHOW STARRING JIMMY FALLON” TALK SHOW - Khoirotul Banat (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This research is an analysis of the flouting maxim in "The Tonight Show Starring Jimmy Fallon" talk show in which Tom Hiddleston was invited as the guest star. The aims of this research are to find out the flouting maxims performed by the guest and to discover the host’s reactions when the guest flouted maxims. In this study, the researchers used descriptive qualitative method, and the data were collected from a video. The transcript text of the utterances between the host and the guest consisting of flouting maxim was the instrument of this research. Then, to find and analyze the flouting maxim showed in the video, the researchers used Grice's theory, the Cooperative Principles consisting of four maxim types: quality, quantity, relation, and manner. The result showed that only three types of flouting maxim were committed by the guest in talk show. The highest flouting maxims found were flouting the maxim of quantity. Further, the study also discovered that the flouting maxims do not always give misunderstandings in conversation. Many flouting maxims were committed in this talk show but the host still understood the conversation and the conversation was still going well.